Pharmacological activities of gamma-terpinene: A review (Research, Society and Development, 2025)
Monoterpenes, such as gamma-terpinene (γ-TPN), exhibit relevant pharmacological effects that make them promising alternatives for the treatment of several clinical conditions. Therefore, the objective of this review was to compile the potential pharmacological effects of γ-TPN in in vitro and in vivo studies. For this purpose, an electronic research study was conducted in June 2025 using the PubMed and Web of Science databases, collecting studies on the pharmacological activities of γ-TPN. Two independent reviewers performed the selection using the Rayyan review application and extracted the main data from the included studies. After applying the eligibility criteria, 13 articles were included in this review. These studies reported eight pharmacological activities, including antibacterial, antiprotozoal, antioxidant, cytotoxic and antitumor, antiplatelet, anti-inflammatory, antihyperalgesic, and nervous system effects. Therefore, γ-TPN presents itself as a pharmacological alternative that can be used in the treatment of various pathologies. However, further studies need to be conducted to investigate the effectiveness and mechanism of action of this monoterpene.